REVIEW: China's transboundary waters: new paradigms for water and ecological security through applied ecology. Issue 5 (30th June 2014) - He, Daming; Wu, Ruidong; Feng, Yan; Li, Yungang; Ding, Chengzhi; Wang, Wenling; Yu, Douglas W.; Crispo, Erika
Summary China is Asia's most important upstream riparian country, sharing 110 rivers and lakes with 18 downstream countries. Consequently, China's management of transboundary water resources must consider both environmental and geopolitical risks. The major threats to and conflicts over international rivers in China revolve around biotic homogenisation due to the installation of transport links, water allocation, water pollution, alteration of natural flow patterns and disruption of fisheries due to the installation of hydropower dams, and droughts and floods exacerbated by climate change. Because these problems have an international component, they fall under China's Peaceful Rise strategy, mandating that transboundary conflicts be resolved amicably as part of the overarching goal of increasing regional economic growth with as little conflict as possible. Science‐backed policy is more likely to result in long term, mutually agreeable solutions; the results of applied ecological research have already resulted in a number of mitigation measures, including setting operational thresholds to reduce the downstream impact of dams, designating protected areas along key river stretches where dams cannot be installed (one dam in a critical location has been cancelled), and the installation of terrestrial protected‐area networks. Synthesis and applications. Applied ecology will continue to play an important role in the diagnosis and resolution of environmental threats to China's transboundary waters. More importantly, applied ecology can inform the development of a transboundary environmental compensation mechanism and regional consultative mechanisms that support informed, cooperative decision‐making for China and its riparian neighbours.